the Responsibility of the Keeper of the Thing Studying in the Algerian Judiciary - Djouabi, Fella (Journal of Legal Studies and Researches, 2022)
The system of compensation for the responsibility, of responsibility of the thing keeper in Article 138 C.C is extremely important. The responsibility of the thing keeper is an objective one, based on a harmful act, the damage, and the causal relationship, but we find differences in the basis for establishing this responsibility in the decisions of the Supreme Court.